Evaluation of the bacteriophage MAC-1 potential to control pseudomonas aeruginosa planktonic cells and biofilms - Aqeel, Moaz; Bukhari, Sayed Muhammad Ata Ullah Shah; Ullah, Hidayat; Hussain, Tahir; Ullah, Aman; Jamal, Muhsin; Nawaz, Muhammad Asif; Andleeb, Saadia; Khan, Khurshaid; Pervez, Sidra; Imran, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Pseudomonas aeruginosa is a pathogenic bacterium that can be considered a high risk to human health due to its remarkable capacity to resist antibiotics, either intrinsically or following the acquisition of resistance genes. P. aeruginosa has been considered a major threat to human health as all the known remedies seem ineffective. Bacteriophages as a natural killer of bacteria can offer alternative therapy for antibiotics. The study aimed to isolate and characterize a lytic bacteriophage against P. aeruginosa (clinically resistant strain/superbug) and to investigate its lytic potential to control bacterial planktonic cells and their biofilms on stainless steel surfaces. A lytic bacteriophage known as MAC-1 was isolated from wastewater against the selected P. aeruginosa-2750 strain. Its host range was moderate and it only infected six isolates. Phage MAC-1 was characterized through transmission electron microscopy and was classified to the Siphoviridae family. It has good heat and pH stability. Its latent time was 24 min with a burst size of about 410 virions per cell. The phage MAC-1 efficacy was determined against P. aeruginosa planktonic cells and biofilms on metallic surfaces. Isolated phage MAC-1 demonstrated promising activity against bacterial planktonic cells as well as in reducing bacterial biofilm biomass formed in 96-well and on stainless steel plates. However, a phage cocktail may be used to avoid resistance and ensure complete eradication of bacterial biofilms.